1977
DOI: 10.1002/path.1711220108
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypoplasia in babies with severe rhesus isoimmunisation: A quantitative study

Abstract: Analysis of lung weights of 96 infants dying with rhesus isoimmunisation has shown that the lung is considerably retarded in its growth. Detailed analysis of the lungs of six babies after pulmonary artery injection showed in all a reduction in airway number and thus acinar and artery number, suggesting arrest in growth before the 16th week of gestation. The alveoli were also of either abnormal number, size or maturity, suggesting a continuing effect in later foetal life. Total lung volume varied from the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…PH was also demonstrated in some instances of hydrops fetalis, as reported by Chamberlain et al (1977), and may have been caused by the thoracic space-occupying effects of large pleural effusions and raising of the diaphragm by tense ascites and gross hepatosplenomegaly. It is suggested that a similar mechanism exists that raises the diaphragm in PH associated with ascites in meconium peritonitis.…”
Section: Discussionmentioning
confidence: 68%
“…PH was also demonstrated in some instances of hydrops fetalis, as reported by Chamberlain et al (1977), and may have been caused by the thoracic space-occupying effects of large pleural effusions and raising of the diaphragm by tense ascites and gross hepatosplenomegaly. It is suggested that a similar mechanism exists that raises the diaphragm in PH associated with ascites in meconium peritonitis.…”
Section: Discussionmentioning
confidence: 68%
“…The latter has been expressed in an increased medial wall thickness as percentage of the external thickness 15,16 . Peripheral extension of muscle into arteries smaller than normal have been observed 7,9,15,16 and the intrapulmonary arteries are smaller than normal but appropriate for the reduced volume of the lung 7,9 . These features form the morphologic basis for the increased pulmonary vascular resistance.…”
Section: Abnormal Lung Development: Pulmonary Hypoplasia Definition Amentioning
confidence: 99%
“…Lung growth can also be impaired by a direct immune mediated injury [10]. Low lung volumes were noted in infants whose mothers underwent their ®rst invasive procedure prior to 24 weeks of gestation [17]; the pulmonary abnormality at follow-up might, therefore, re¯ect the severity of the fetal condition [10] and/or indicate that the invasive procedures were carried out at a critical stage of lung growth.…”
Section: Morbiditymentioning
confidence: 99%